Human Metapneumovirus Infection Inhibits Cathelicidin Antimicrobial Peptide Expression in Human Macrophages - Li, Youxian; Østerhus, Stine; Johnsen, Ingvild B. (Frontiers in Immunology, 2018)
Human cathelicidin antimicriobial peptide (CAMP) is a critical component of host innate immunity with both antimicrobial and immunomodulatory functions. Several pathogens have been shown to downregulate CAMP expression, yet it is unclear if such modulation occurs during a viral infection. In this study, we showed that infection with human metapneumovirus (hMPV), one of the leading causes of respiratory tract infections in young children, strongly suppressed basal and vitamin-D induced CAMP expression in human macrophages. hMPV-mediated suppression of CAMP did not correlate with reduced transcriptional expression of key vitamin D signaling components such as CYP27B1 or VDR, suggesting a vitamin D-independent mechanism. Blocking interferon-signaling pathways did not reverse hMVP-mediated suppression of CAMP, indicating that the suppressive effect is largely interferon-independent. Instead, we identified C/EBPα as the key modulator of hMPV-mediated suppression of CAMP. hMPV infection strongly repressed the expression of C/EBPα, and a knockdown study confirmed that C/EBPα is critical for CAMP expression in human macrophages. Such modulation of CAMP (and C/EBPα) could be reproduced by TLR1/2 ligand treatment in human macrophages, suggesting a common mechanism underlying pathogen-mediated downregulation of CAMP through C/EBPα. This study opens up a new understanding of altered human antimicrobial responses following infections.